Impact of PCV13 on Serotype 3 Invasive Pneumococcal Disease and Nasopharyngeal Carriage in Massachusetts' Children. (4th October 2017) - Lapidot, Rotem; Shea, Kimberly M; Little, Brent A; Yildirim, Inci; Pelton, Stephen I
Abstract: Background: Although a substantial decline in overall vaccine serotype invasive pneumococcal disease (IPD) incidence has been observed following immunization with PCV7 and subsequently PCV13, the reported effectiveness for individual vaccine serotypes has varied. Reported effectiveness of PCV13 for serotype 3 (ST3) disease has differed by study design and geography, with a wide range of estimates including zero. We assessed the impact of PCV13 on ST3 IPD cases and nasopharyngeal (NP) carriage in Massachusetts' children. Methods: Cases of ST3 IPD in children <18 years were identified via enhanced passive surveillance in conjunction with the Massachusetts Department of Public Health from 2002 to 2016. NP Carriage of ST3 in children aged 3 months to <7 years was identified via an active surveillance network of pediatric practices in Massachusetts from 2007 to 2014. Annual incidence rates of ST3 IPD were calculated using US Census estimates as population denominators. Annual prevalence rates of carriage were calculated using the surveillance population. We compared age distribution, clinical syndromes, presence of comorbidities and vaccination status for IPD cases and age distribution of children with ST3 carriage before and after PCV13 implementation. Results: Overall 47 cases of ST3 IPD were identified from 2002 to 2016; the incidence of ST3 IPD before and after PCV13 was 0.23 and 0.20 per 100, 000 children respectively (incidence rate ratio [IRR] = 1.13, 95% CI 0.62–2.05). There were no differences in age distribution, clinical syndrome or presence of comorbidities among ST3 IPD cases before and after PCV13. The majority (9/13) of post PCV13 ST3 IPD cases occurred among children who were fully vaccinated. No association was seen between date of last PCV13 dose and time of IPD to suggest waning immunity. Prevalence of ST3 carriage among children aged 3 months to <7 years before and after PCV13 implementation was 0.19 and 0.64 respectively (Prevalence ratio [PR] = 0.3, 95% CI 0.11–0.83). Conclusion: Six years after PCV13 implementation, no significant changes in ST3 IPD incidence, age distribution, clinical syndrome or presence of comorbidity among cases in children <18 years of age were observed. An increase in NP carriage in children <7 years of age was observed. Disclosures: K. M. Shea, Pfizer, Inc: Consultant and Grant Investigator, Consulting fee and Grant recipient; S. I. Pelton, Pfizer: Board Member and Grant Investigator, Consulting fee, Research grant and Speaker honorarium; Merck vaccines: Board Member, Consulting fee and Speaker honorarium; GSK: Board Member, Consulting fee and Speaker honorarium; Sequiris: Board Member, Consulting fee and Speaker honorarium